The effect of plant closure on crime - Mari Rege; Torbjørn Skardhamar; Kjetil Telle; Mark Votruba (Statistics Norway, Research Department, 2009)
We estimate the effect of exposure to plant closure on crime using an individual-level panel data set containing criminal charges for all unmarried and employed Norwegian men below the age of 40. Men originally employed in plants that subsequently closed are 14 percent more likely to be charged of a crime than comparable men in stable plants. There is no difference in charge rates prior to closure, supporting a causal interpretation of our result. Within crime categories, we find no effect of plant closure on property crime, perhaps because closure has a small and insignificant effect on subsequent earnings. We estimate an effect of plant closure on categories of non-acquisitive crime, suggesting a role for mental distress or idleness. A role for idleness is supported by evidence that the effects of plant closure on crime tend to be more pronounced for crimes committed during the week than on weekends.
Keywords: J12; J63; J65; 330; crime; plant closure; plant downsizing; displacement